KING OF IMERETI SOLOMON I AND THE PROJECT OF RESETTLEMENT KABARDIANS TO GEORGIA - Natsvaladze , Mamuka (Collection of scientific papers «ΛΌГOΣ», 2023)
This article presents unknown fragments of political and diplomatic relations between Georgians and Kabardians in the 70-80s of the XVIII century. It reviews the project of Erekle II King of Kartli-Kakheti to resettle Kabardians to Georgia. As it was observed not only Erekle II King of Kartli-Kakheti, but also Solomon I King of Imereti participated in the project. Accordingly, it is confirmed that the project to resettle Kabardians to Georgia belonged not only to Erekle II King of Kartli-Kakheti, but also to Solomon I King of Imereti.